Improving Grid Network Operations Through an Improved Energy Market. Issue 3 (2nd July 2020) - Haynes, David; Corns, Steven
Abstract: Distributed power generation can lead to overvoltage conditions, potentially damaging devices connected to the electrical grid. A method to improve the management of distributed power is presented to limit damaging overvoltage conditions using a transactive energy market and a Tabu Ant Colony Optimizer to manage activity on the distribution network. Overvoltage situations representing the intermittent power contributions from distributed sources were modeled on this network, and the results of current control methods were compared to those obtained using the developed Tabu Ant Colony Optimizer. Existing real time control methods resulted in overvoltages exceeding six percent above nominal, while the Tabu Ant Colony Optimizer resulted in overvoltage of less than three percent. Using this automated energy market mechanism as a management layer for the distribution network demonstrates how computational intelligence approaches can assist engineering managers responsible for these complex systems.